Synthesis of molecularly imprinted polymer for glucose binding - Nurul Atiqah, Abdul Hamid (2014)
Molecularly imprinted polymer (MIP) is an attractive technique for the synthesis of highly selective polymeric receptors having artificial generated recognition sites. These materials were synthesized with polymerizable functional monomers and crosslinker that were surrounded around the template molecule. After polymerization, a template molecule was removed leaving in the polymer selective recognition sites with shape, size and functionalities complementary to the template. This study presents a synthesis of MIP selectively for glucose binding. Glucose phosphate salt (GPS) was used as a template molecule with poly(allylamine hydrochloride) (PAA.HCl) as a functional monomer. Three types of crosslinkers which are epichlorohydrin (EPI), ethylene glycol diglycidyl ether (EDGE) and glycerol diglycidyl ether (GDE) were studied during the MIP synthesis. MIP prepared using EPI as a crosslinking showed the highest glucose binding capacity around 0.84 mg glucose/mg dried gel. The binding capacity of MIP prepared using EGDE and GDE are 0.78 mg glucose/mg gel and 0.38 mg glucose/mg gel respectively. It is also found that the increase on GPS monomer concentration will contribute to increase in glucose binding